2004
DOI: 10.1097/00007691-200406000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of 6-Mercaptopurine in Patients with Inflammatory Bowel Disease

Abstract: Proper prospective pharmacokinetic studies of 6-mercaptopurine (6-MP) in inflammatory bowel disease (IBD) patients are lacking. As a result, conflicting recommendations have been made for metabolite monitoring in routine practice. The authors have evaluated 6-MP pharmacokinetics in IBD patients, including the genetic background for thiopurine methyltransferase (TPMT). Red blood cell (RBC) 6-thioguanine nucleotide (6-TGN) and 6-methylmercaptopurine ribonucleotide (6-MMPR) concentrations were measured in 30 IBD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 19 publications
7
94
1
Order By: Relevance
“…Furthermore, as IMPDH II is not involved in the hypoxantine guanine phosphoribosyl transferase salvage pathway of purine synthesis, MMF does not inhibit key enzymes of other cell tissues, which is different from other immunosuppressants that are nowadays used for treatment of MG patients (Patel et al, 2006;Schneider-Gold et al, 2006). For example, azathioprine exerts its immunosuppressive effect on both the de novo pathway of purine synthesis and the hypoxantine guanine phosphoribosyl transferase salvage pathway; thereby causing not only inhibition of B-and T-lymphocytes proliferation but also inhibition of purine synthesis in other tissues leading among other side effects to bone marrow suppression (Derijks et al, 2004;Gunnarsdottir and Elfarra, 1999). On the other hand, cyclosporine only inactivates T-helper lymphocytes by blockade of interleukin-2 signaling and therefore does not interfere directly with B-lymphocyte proliferation (Hagberg et al, 1988).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, as IMPDH II is not involved in the hypoxantine guanine phosphoribosyl transferase salvage pathway of purine synthesis, MMF does not inhibit key enzymes of other cell tissues, which is different from other immunosuppressants that are nowadays used for treatment of MG patients (Patel et al, 2006;Schneider-Gold et al, 2006). For example, azathioprine exerts its immunosuppressive effect on both the de novo pathway of purine synthesis and the hypoxantine guanine phosphoribosyl transferase salvage pathway; thereby causing not only inhibition of B-and T-lymphocytes proliferation but also inhibition of purine synthesis in other tissues leading among other side effects to bone marrow suppression (Derijks et al, 2004;Gunnarsdottir and Elfarra, 1999). On the other hand, cyclosporine only inactivates T-helper lymphocytes by blockade of interleukin-2 signaling and therefore does not interfere directly with B-lymphocyte proliferation (Hagberg et al, 1988).…”
Section: Discussionmentioning
confidence: 98%
“…We decided to use the thiopurine metabolite concentrations after 3 months because steady-state 6-TGN concentrations may be anticipated following 2 months of use. 15 To quantify the concentrations of 6-TGN and 6-MMP in the human red blood cell (RBC), a high-performance liquid chromatography assay was used as recently described. 16,17 It is suggested that the 6-MMP/6-TGN ratio may be a predictor for therapeutic efficacy, as a ratio above 11 is associated with therapeutic inefficacy.…”
Section: Characteristics Of Thiopurine Usementioning
confidence: 99%
“…[2][3][4] A high ratio can result in treatment failure and toxic side effects. 3,[5][6][7][8][9][10] Although azathioprine is widely used in the management of inflammatory bowel disease (IBD) approximately 9% of patients are resistant to thiopurine therapy. 4,11 These patients are unable to achieve therapeutic concentrations of 6-TGN and accumulate 6-MMPR to hepatotoxic concentrations.…”
Section: Introductionmentioning
confidence: 99%